Virtual screening of pyrazole derivatives of usnic acid as new class of anti-hyperglycemic agents against PPARγ agonists - Roney, Miah; Issahaku, Abdul Rashid; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer, 2023)
The finest sources of therapeutic agents are natural products, and usnic acid is a secondary metabolite derived from lichen that has a wide range of biological actions, including anti-viral, anti-cancer, anti-bacterial, and anti-diabetic (hyperglycemia). Based on the hyperglycemia activity of UA, this work seeks to identify new anti-hyperglycemia medicines by virtual screening of pyrazole derivatives of UA. Seven hit compounds (Compounds 1, 5, 6, 7, 17, 18 and 33), which finally go through docking-based screening to produce the lead molecule, were identified by the physicochemical attributes, drug-likeliness, and ADMET prediction. The docking score for the chosen compounds containing PPARγ agonists ranged from -7.6 to -9.2 kcal/mol, whereas the docking goal for compounds 5, 6, and 7 was -9.2 kcal/mol. Based on the binding energy and bound amino acid residues as well as compared to the reference compound, compound-6 considered as lead compound. Furthermore, the MD simulation of 3CS8-Compound-6 and 3CS8-Rosiglitazone complexes were performed to verify the stability of these complexes and the binding posture acquired in docking experiments. The compound-6 had strong pharmacological characteristics, bound to the PPARγ agonist active site, and was expected to reduce the activity of the receptor, according to the virtual screening results. It must be justified to conduct both in-vitro and in-vivo experiments to examine the efficacy of this compound.